2011
DOI: 10.1111/j.2041-1626.2011.0087.x
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic bone cavity: case series involving children and adolescents

Abstract: Clinical and radiographic diagnoses associated with surgical exploration are the most important treatment options in order to avoid radical surgery or unnecessary endodontic treatment, mainly when idiopathic bone cavities are detected in children and adolescents. Further studies aimed at elucidating the etiopathogenesis of this condition and defining the most appropriate treatment should be conducted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 21 publications
4
33
0
Order By: Relevance
“…In the oral cavity, the literature has shown the mandible to be the bone most affected. As for the age group affected by this entity, the vast majority of studies have reported an age range between 15 and 20 [7][8][9] . In the quest to find other studies reporting SBC in children, as in the present case, only one report was found for the same age group, associated with a previous trauma 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the oral cavity, the literature has shown the mandible to be the bone most affected. As for the age group affected by this entity, the vast majority of studies have reported an age range between 15 and 20 [7][8][9] . In the quest to find other studies reporting SBC in children, as in the present case, only one report was found for the same age group, associated with a previous trauma 10 .…”
Section: Discussionmentioning
confidence: 99%
“…In the quest to find other studies reporting SBC in children, as in the present case, only one report was found for the same age group, associated with a previous trauma 10 . Other SBC studies in children relate to children 10 years of age, or older 7,9 .…”
Section: Discussionmentioning
confidence: 99%
“…It is a non-neoplastic osseous lesion first described by Lucas and Blum in 1992 [1][2][3]. In 1946, diagnostic criteria specified the absence of epithelial lining and a bony wall surrounding the lesion as characteristics specific to the SBC [4][5][6][7][8][9][10][11]. Ninety percent of SBC cases are reported to be in long bones such as the proximal humerus and femur, however, simple bone cysts only comprise one percent of all cysts affecting the jaw [7].…”
Section: Introductionmentioning
confidence: 99%
“…Commonly, though, SBC's are detected during the second decade of life, while some sources report no predilection for male or female, others report a male predominance [5,6,17]. Radiographically, the lesion appears as a unilocular, radiolucent image, with a cortical margin of varying thickness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation